The algorithm and the city: platform labour and the urban environment. (1st January 2020) - Huws, Ursula
Abstract : Introducing this special issue, the author starts by summarising the rapid development of algorithmic management in urban environments at the end of the second decade of the 21st century. There is a complex mutual interaction between the governance of cities and the spread of digital means for managing the delivery of goods and services to residents. This leads to a simultaneous reconfiguration of public spaces on the one hand, and a transformation of economic and social relationships on the other. The use of digital apps for service delivery, in particular, puts the platform at the centre of the relationship between the workers who deliver these services and the consumers who purchase them, in the process giving it access to a large body of data it can use to fuel its further expansion and control of labour. This development displaces not only work that was previously carried out within the scope of formal, regulated employment relationships (based on waged labour and with statutory rights and benefits) but also work previously carried out in the informal sector. The contributions to this special issue aim to explain and describe the rapidly evolving situation as it stood in 2019, at the brink of the global coronavirus epidemic. At the time of publication (after these articles were written) it is becoming clear that this epidemic is strengthening and accelerating some of these trends, while, in the short term, deflecting others. The analyses presented here provide a vital underpinning for any future research that seeks to understand the social, economic and political impacts of the coronavirus crisis on cities and their inhabitants.